2018
DOI: 10.1016/j.jacc.2018.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes From Patients With Type 2 Diabetes Induce Endothelial Dysfunction Via Arginase I

Abstract: This study demonstrates a novel mechanism behind endothelial dysfunction in T2DM that is induced by RBC arginase I and ROS. Targeting arginase I in RBCs may serve as a novel therapeutic tool for the treatment of endothelial dysfunction in T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(181 citation statements)
references
References 19 publications
14
164
2
1
Order By: Relevance
“…Abnormal NO levels have been reported in vascular pathological conditions (Bondonno et al, 2016), and intervention in NO signaling can effectively prevent various vascular disorders, including endothelial dysfunction, vascular inflammation and vascular stiffness (Bondonno et al, 2016;Batko et al, 2019;Chen et al, 2019). Furthermore, excessive arginase activation can down-regulate NO production by reducing NOS availability through competition for their common substrate L-arginine (Bhatta et al, 2017;Zhou et al, 2018). This notion is supported by our results showing that HGWWD decreased endothelial arginase activity and aortic arginase 1 expression in STZ mice (Figure 4).…”
Section: Discussionsupporting
confidence: 74%
“…Abnormal NO levels have been reported in vascular pathological conditions (Bondonno et al, 2016), and intervention in NO signaling can effectively prevent various vascular disorders, including endothelial dysfunction, vascular inflammation and vascular stiffness (Bondonno et al, 2016;Batko et al, 2019;Chen et al, 2019). Furthermore, excessive arginase activation can down-regulate NO production by reducing NOS availability through competition for their common substrate L-arginine (Bhatta et al, 2017;Zhou et al, 2018). This notion is supported by our results showing that HGWWD decreased endothelial arginase activity and aortic arginase 1 expression in STZ mice (Figure 4).…”
Section: Discussionsupporting
confidence: 74%
“…2 There are complex pathways involved in the mechanisms of vascular calcification/aging in diabetes, including HG regulation in both endothelial and VSMC layers. 3,4,7,19 Vascular endothelial dysfunction is associated with diabetic conditions, 6,7,20 while little is known about the mechanisms driving calcification/senescence of VSMCs under diabetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…44 Interestingly, arginase is up-regulated in erythrocytes in type 2 diabetes-an important comorbidity in patients with STEMI. 45,46 Accordingly, it was recently demonstrated that erythrocytes from both mice and patients with type 2 diabetes markedly impair recovery of cardiac systolic function, increase left ventricular end-diastolic pressure and increase infarct size following IR in comparison with erythrocytes from control mice or healthy humans. 46 The underlying mechanism behind this effect was increased arginase activity in erythrocytes which led to a decrease in NO production.…”
Section: Erythrocytesmentioning
confidence: 99%